1989
DOI: 10.1002/dvg.1020100307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of juvenile hormone on the ecdysone response of Drosophila Kc cells

Abstract: Drosophila Kc cells are ecdysone-responsive: hormone treatment leads rapidly to increased synthesis of several ecdysone-inducible polypeptides (EIPs) and to commitment to eventual proliferative arrest. Later, the treated cells undergo morphological transformation, cease to proliferate, and develop new enzymatic activities, notably, acetylcholinesterase (AChE) activity. These responses have proven useful as models for studying ecdysone action. Here we report the sensitivity of Kc cells to another important inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 82 publications
2
28
1
Order By: Relevance
“…Earlier studies (Lezzi and Wyss 1976;Cherbas et al 1989) showed the modulation of ecdysteroid-induced effects by JH and JHAs in Drosophila, Chironomus, and Plodia cells. More recently, Soin et al (2008) tested the three best known JHAs, methoprene, fenoxycarb, and pyriproxyfen, with transformed lepidopteran Bm5 and dipteran S2 cells.…”
Section: Insect Cell Cultures In Screening For Novel Insecticide Actimentioning
confidence: 99%
“…Earlier studies (Lezzi and Wyss 1976;Cherbas et al 1989) showed the modulation of ecdysteroid-induced effects by JH and JHAs in Drosophila, Chironomus, and Plodia cells. More recently, Soin et al (2008) tested the three best known JHAs, methoprene, fenoxycarb, and pyriproxyfen, with transformed lepidopteran Bm5 and dipteran S2 cells.…”
Section: Insect Cell Cultures In Screening For Novel Insecticide Actimentioning
confidence: 99%
“…There has been considerable contemplation over to what extent the methoprene receptor (MET protein) is the same or a different cellular target than is the target of the endogenous, ring gland-produced farnesoate methyl esters (Cherbas et al, 1989;Wilson et al, 2003). A number of lines of evidence indicate that an endogenous signaling pathway during larval development and metamorphosis exists other than, or in addition to, the MET protein pathway:…”
Section: Met Proteinmentioning
confidence: 99%
“…(The term juvenoids includes endogenous compounds and chemical analogs with JH-like activity.) Studies in several insect species indicate that juvenoids can modulate cellular responses to 20E [Chihara and Fristrom, 1973;Wyss, 1976;Mitsui and Riddiford, 1978;Levine et al, 1986;Booker and Truman, 1987;Truman and Reiss, 1988;Cherbas et al, 1989;Jacobs and Weeks, 1990;Prugh et al, 1992]. We tested the hypothesis that juvenoid-induced lethality results from interfering with the function of the Broad Complex (BRC), a gene essential for transducing 20E signals into the metamorphic development of larval and imaginal tissues, including the epidermis, salivary glands, central nervous system (CNS), gut, and musculature [Kiss et al, 1988;White, 1991, 1992].…”
Section: Introductionmentioning
confidence: 99%